Up from the grave ebook A night huntress novel. - Frost, Jeaniene (Night Huntress, 2014)
There's always one more grave to dig Lately, life has been unnaturally calm for vampires Cat Crawfield and her husband, Bones. They should have known better than to relax their guard, because a shocking revelation sends them back into action to stop an all-out war . . . A rogue CIA agent is involved in horrifying secret activities that threaten to raise tensions between humans and the undead to dangerous heights. Now Cat and Bones are in a race against time to save their friends from a fate worse than death . . . because the more secrets they unravel, the deadlier the consequences. And if they fail, their lives—and those of everyone they hold dear—will be hovering on the edge of the grave.